PENGARUH IKLAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA DI KRIDA DINAMIK AUTO NUSA CABANG SUMBAWA: Indonesia - Andi Rusni; Muhammad Marwan (Journal of Management and Business, 2021)
This study aims to examine the effect of advertising and brand image on purchasing decision for Honda Motorcycle at Krida Dinamik Auto Nusa. This research is quantytatif data that use is primer. The sourch of the data is eksternal which is obtain depend on quisioner from 96 respondend. The method to obtain the sample is purposive sampling with non-probability sampling. Validaty test instrumen with SPSS. Double regresi liniear Analysis is used to test hipotesis of this reseach.This research show that : (1) advertising variable has impact but not significant of Buying Decision of Honda Motorcycle in Krida Dinamik Auto Nusa. (2) Brand Image variable has positive impact to Buying Decision of Honda Motorcycle in Krida Dinamik Auto Nusa.